The Phenomenon of Cyberbullying on Social-Media: Cyberbullying on the Instagram Account @tissabiani - Pratiwi, Meisyi Naishilla Defti (International Journal of Science and Society, 2025)
Cyberbullying has become a significant issue in the world of social media, particularly on the Instagram platform. The study looked at the phenomenon of cyberbullying involving @tissabiani accounts with Fuji fans. Through online observation using qualitative approaches and content analysis methods, interactions in comments and direct messages are analyzed to understand the patterns of interactions and reactions that occur to explore the phenomenon of cyberbullying on social media. The findings showed a pattern of verbal attacks and direct attacks that caused tension between the two sides. Anonymity and fanaticism are what trigger cyberbullying in computer-mediated interactions and communications. The response from social media platforms and communities highlights the complexities and challenges of dealing with cyberbullying. User protection, educational approaches, and policies that are responsive to online verbal abuse are important in resolving these kinds of conflicts. Collaborative efforts from various parties are expected to reduce incidents and raise awareness of the negative impact of cyberbullying.